Conquering maternal mortality: skill development in medical curriculum - A, Parimala; Sharma, Nidhi; Jayashree, K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Maternal Mortality Rate remains to be high in developing countries despite the advances made in the modern world. A medical student needs to understand the basic clinical subjects and in a short span of one year translate it into patient care. A skill development method was initiated in the final year curriculum of medical students to integrate the basic knowledge of labor with the final outcome of reducing maternal mortality rate. Methods: The skills were demonstrated on mannequins and simulation models of difficult situations in labour were provided. The study was conducted in Saveetha Medical College in the Department of Obstetrics and Gynaecology in May 2015 as a one day hands on workshop for medical undergraduate students. One hundred and fourteen medical students conducted normal labor, applied forceps and ventouse, sutured episiotomies and perineal tear and performed a drill on active management of third stage of labor on training mannequins. All the basic didactic teaching and its translation into clinical skills were tested pertaining to the problem of parturition. Plenary discussion of each demonstrable skill was done by a galaxy of experts. This was followed with Mind Mapping of concepts developed. Pretest and posttest helped the teaching faculty to assess the impact of knowledge generated. Feedback was obtained to improvise the existing teaching method and develop new teaching tools. Results: The students were able to comprehend Conduct of Labor from its basics and decide on the relevant clinical implications. The case based skill demonstrations done on instrumental delivery, episiotomy suturing, clinical pelvimetry, active management of third stage of labor and monitoring of labor using partogram gave students hands on experience and improved their practical knowledge. Conclusion: Skill Development in conduct of labour helps medical students to understand the clinical implications better. A well trained medical student can thus help to reduce maternal mortality rate in developing countries.